PENGARUH RISIKO BISNIS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL DAN NILAI PERUSAHAAN PADA PERUSAHAAN FARMASI DI BURSA EFEK INDONESIA - Ni Luh Putu Wiagustini; Ni Putu Pertamawati (Faculty of Economics and Business Udayana University, 2015)
This study aim is to determine the effect of business risk and the size of company on capital structure and firm value. The population of this study were 9 companies in pharmaceutical sub-sectors listed on the Indonesia Stock Exchange. Sample size was determined by census method-taking all population as sample. This study used secondary data obtained from the Indonesia Stock Exchange (www.idx.co.id) and ICMD in 2006-2013. The study implemented path analysis technique. The results show that, firstly, business risk and firm size is have a positive and significant impact on capital structure. Secondly, business risk has a negative and significant effect on company value, whereas size of the company has a positive and significant effect on company value. On the other hand, and capital structure has positive yet not significant effect company value. Thirdly, capital structure emerges as mediating variable in the affect of business risk on the company value